Consultation in the Practice of Forensic Medicine - Şener, Mustafa Talip; Kök, Ahmet Nezih (The Bulletin of Legal Medicine, 2011)
Consultation is considerably important for forensic medicine specialists in the assessment of diagnosis, treatment and complications. This study aimed to determine the most commonly needed branches for consultations and the subject of consultation. The reports issued by Atatürk University, Medicine Faculty Department of Forensic Medicine between 01.01.2006 and 31.12.2011 were investigated retrospectively. Age and gender of cases, consultation subject and needed branches were investigated. The average age of the cases was 30 (sd: ±16.403) years and the age range was between 1 and 91 years. Of cases, 78.1% (n=6301) was male and 21.9% (n=1767) was female. In evaluation of 80.1% (n= 6461) of cases there was no need for consultation, while 19,9% (1607) of cases were consulted to at least one medical branch. The most commonly consulted branch was radiology as in 39.1% (n=700) cases, followed by 17.8% (n=319) cases from psychiatry and child and adolescent psychiatry specialists. Age estimation, disability assessment and malpractice cases were the most commonly consulted cases. Consultation for forensic medicine specialists provides an important contribution to the assessment's and enhance the objectivity and quality forensic reports.Key words: Forensic medicine, legal cases, referral and consultation
Keywords: forensic medicine; legal cases; referral and consultation